1998
DOI: 10.1042/bj3300175
|View full text |Cite
|
Sign up to set email alerts
|

Human glutathione transferase A4-4: an Alpha class enzyme with high catalytic efficiency in the conjugation of 4-hydroxynonenal and other genotoxic products of lipid peroxidation

Abstract: A sequence encoding a novel glutathione transferase, GST A4-4, has been identified in a human fetal brain cDNA library. The protein has been produced in Escherichia coli after optimization of the codon usage for high-level heterologous expression. The dimeric protein has a subunit molecular mass of 25704 Da based on the deduced amino acid composition. Human GST A4-4 is a member of the Alpha class but shows only 53% amino acid sequence identity with the major liver enzyme GST A1-1. High catalytic efficiency wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
241
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 353 publications
(258 citation statements)
references
References 35 publications
12
241
0
Order By: Relevance
“…The fact that the transfected cells had significantly lower basal GSH concentrations than the control cells implies an increased utilization of GSH due to high expression and activity of the hGSTA4-4 enzyme and associated demand for GSH. The somewhat higher GSH peroxidase activity toward CumOOH in the hGSTA4 cells may also have reflected the higher expression of the hGSTA4-4 protein, which has catalytic activity towards this substrate (Hubatsch et al, 1998) and which likely placed further demands on constitutive cellular GSH levels. In contrast, GSTs do not catalyze the GSH-mediated reduction of H 2 O 2 , which is primarily catalyzed by cytosolic seleniumdependent GSH peroxidase (Hayes and Pulford, 1996), and whose activities did not differ among hGSTA4 and control cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that the transfected cells had significantly lower basal GSH concentrations than the control cells implies an increased utilization of GSH due to high expression and activity of the hGSTA4-4 enzyme and associated demand for GSH. The somewhat higher GSH peroxidase activity toward CumOOH in the hGSTA4 cells may also have reflected the higher expression of the hGSTA4-4 protein, which has catalytic activity towards this substrate (Hubatsch et al, 1998) and which likely placed further demands on constitutive cellular GSH levels. In contrast, GSTs do not catalyze the GSH-mediated reduction of H 2 O 2 , which is primarily catalyzed by cytosolic seleniumdependent GSH peroxidase (Hayes and Pulford, 1996), and whose activities did not differ among hGSTA4 and control cells.…”
Section: Discussionmentioning
confidence: 99%
“…Of these enzyme systems, GST is a predominate mechanism for protection against 4-HNE toxicity in mammalian liver (Hartley and Petersen, 1997;Gardner et al, 2003). Interestingly, the major human liver GST isoform, hGSTA1-1, is relatively inefficient at conjugating 4-HNE (K m = 50 mM, k cat /K m = 0.058 s −1 mM −1 (Hubatsch et al, 1998;Coles and Kadlubar, 2005) and other alkenal substrates. However, another alpha class isoform, hGSTA4-4, appears to be the most efficient human GST isoform that mediates 4-HNE conjugation with a K m of 49 μM and a rapid k cat/ K m of 2.7 s −1 mM −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately attempts in multiple laboratories to demonstrate glutathione S-transferase enzyme activity for Ure2 have been unsuccessful (7,16,20). Although negative results are rarely reported in detail, the lack of success might derive from inherent instability in the enzyme, an observed characteristic of glutathione S-transferases, or from performing the assay with substrates that are not the preferred ones for the putative transferase (25)(26)(27)(28). The difficulties experienced in attempts to assay an enzyme activity prompted us to take a step backward from in vitro assays and ask more simply whether Ure2 is required for protection of cells against the growth-inhibitory effects of compounds reported to be glutathione S-transferase substrates in other organisms.…”
Section: Ure2 Is Required For Protection Against Heavy Metals-ure2mentioning
confidence: 99%
“…The function of rGST 8-8 has not been elucidated in the brain regions where we have detected differential expression, and these brain regions are known to be important in the brain reward pathway. Because GSTs are multifunctional proteins that are involved in transport and biosynthesis of endogenous compounds and play a defensive role against oxidative damage as well as neuroprotection (Danielson et al, 1987;Hubatsch et al, 1998;Singhal et al, 1994), they could be playing a role in these rat brain regions that has yet to be discovered. It has been shown that alcohol exposure alters the glutathione/glutathione transferase (Schnellmann et al, 1984) and the glutathione/glutathione peroxidase-1 systems (Bailey et al, 2001) in response to ethanol-related oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to mGSTA4 and hGSTA4, rGST 8-8 seems to belong to a special subgroup of GSTs involved in the detoxification of highly cytotoxic compounds produced by lipid peroxidation, radical reactions, and other reactions elicited by oxidative stress (Berhane et al, 1994;Hubatsch et al, 1998;Singhal et al, 1994). Previous studies have also demonstrated that dopamine and other physiologically relevant catecholamines are inactivated by human GSTs Hubatsch et al, 1998;Segura-Aguilar et al, 1997). Therefore, GSTs are of interest to the study of alcoholism because of their relevance to oxidative stress and catecholamine inactivation.…”
mentioning
confidence: 99%